2004
DOI: 10.1021/ma048103f
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Complexation of Poly(Ethylene Glycol) with α−Cyclodextrin

Abstract: Low-molecular-weight liquid poly(ethylene glycol) (PEG) spontaneously forms an inclusion compound (IC) when combined with R-cyclodextrin (R-CD) powder at room temperature. This process can be followed with wide-angle X-ray diffraction (WAXD). The WAXD data shows that the R-CD crystals undergo a solid-state crystal-crystal transformation from the cage to the channel crystal structure upon IC formation over a period of about 8 h. The time dependence of the 2θ ) 20°R-CD channel structure X-ray peak can be describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
64
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 19 publications
(61 reference statements)
5
64
0
Order By: Relevance
“…The diffraction patterns of these nanowebs containing various weight ratios of a-CD-PEG-IC are shown in Figure 2 d-f. PEO is a semicrystalline polymer with diffraction peaks at 2q = 198 and 238 (Figure 2 c). The characteristic peaks of the a-CD channel structure [24,25] at 2q values of approximately 208 and 138 were observed for all a-CD-PEG-IC/PEO nanowebs. In addition, an increased peak intensity was observed for the nanowebs containing a high proportion of a-CD-PEG-IC in the matrix.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The diffraction patterns of these nanowebs containing various weight ratios of a-CD-PEG-IC are shown in Figure 2 d-f. PEO is a semicrystalline polymer with diffraction peaks at 2q = 198 and 238 (Figure 2 c). The characteristic peaks of the a-CD channel structure [24,25] at 2q values of approximately 208 and 138 were observed for all a-CD-PEG-IC/PEO nanowebs. In addition, an increased peak intensity was observed for the nanowebs containing a high proportion of a-CD-PEG-IC in the matrix.…”
mentioning
confidence: 92%
“…The powder diffractogram of a-CD-PEG-IC has characteristic strong reflections at 2q values of approximately 208 and 138, arising from the channel packing and not the cage structure of unmodified a-CD (Figure 2 a). [24,25] The electrospinning of a-CD-PEG-IC nanofibers is not possible because of their crystalline nature and the low molecular weight of the PEG. Therefore the PEO polymer matrix was chosen to be used as a carrier for three reasons: 1) it is easy to electrospin PEO nanofibers, and PEO has been shown to be a good carrier matrix for both inorganic compounds and polymers that cannot be electrospun by themselves, [26][27][28][29][30] 2) it has the same chemical structure as PEG, and 3) PEO nanofibers may have many uses in various applications.…”
mentioning
confidence: 99%
“…Recently, the complex formation of CDs with some polymers in bulk have been reported by some groups. [26,27] It has been reported that the complex formation of CD in bulk was also selectively adjusted to the cross-sectional area of the polymers. Previously, we reported that CDs form inclusion complexes with polybutadiene (PB) to give inclusion compounds in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this amphiphile is very suitable because its structure presents well-defined regions that show differential bindings with -CD in aqueous solution. 39 Herein we report a combined X-ray powder diffraction (XRPD), high resolution electron transmission microscopy (HRTEM), and 13 C CP/MAS NMR study of the solid supramolecular polyrotaxane formed between Igepal CO-520 and -CD, supported by single crystal structural analysis. Moreover, we confirm the obtained structure and stoichiometry by comparison of the 1 H NMR spectra of several -CD pseudorotaxanes prepared from Igepals with different numbers of oligo(oxyethylene) groups (n ) 5, 9, and 40) in solution.…”
Section: Introductionmentioning
confidence: 98%